The condition of the Yemenis in Egypt after the conquest 20AH 640 AD - العلو فراس; محسن يونس (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The Yemenis contributed greatly to the establishment of the Arab Islamic state, and The spread of Islam in many countries, many Yemenis participated as commanders of companies in the armies of the Islamic conquest in eliminating the Persian and Roman empires. The Yemenis also contributed to the conquest of the Levant, Iraq, Egypt and other countries, yemeni tribes in the Egyption cities, and they worked to contribute to the organization of administrative, economic and social affairs in them, Among them were warriors, Judges, administrators and economists. They also introduced their customs and traditions to the Egyptian society, so they contributed to organizing the affairs of Egypt and they had amajor role in it, like other countries that the armies of the Arab conquest entered Islamic.